The Effect of the Round Robin Learning Model on Collaboration Skills Among Students in Grade IV of MIN 1 West Lampung - Fiteriani, Ida; Baharudin, Baharudin; Setiawan, Andri (Continuous Education: Journal of Science and Research, 2025)
Collaborative skills are essential for learning. Teacher-centered learning often leads to students lack of active participation in learning activities, resulting in low collaborative skills. One way to improve students collaborative skills is by implementing a round-robin learning model. This model provides equal opportunities for all students to learn in groups, preventing any single student from dominating. This study aimed to determine the effect of the round-robin learning model on students' collaborative skills. This study was conducted at MIN 1 West Lampung. The research method used was a quasi-experimental design. Sampling was conducted using a purposive sampling technique, with 65 students each in the experimental and control classes. The instrument used was a collaboration skills questionnaire. This study shows the results of the post-test data hypothesis test using an independent sample t-test with a significance level of 5% (0.05) showing a Sig. (2-tailed) value of 0.038 which means that there is a rejection of H0 and acceptance of H1. Based on the results of the hypothesis test, it can be concluded that there is an influence of the round robin learning model on improving collaboration skills between students in class IV MIN 1 West Lampung.